Bidirectional relationship between sleep and sedentary behavior in adults with overweight or obesity: A secondary analysis. Issue 1 (26th March 2021) - Imes, Christopher C; Bizhanova, Zhadyra; Kline, Christopher E; Rockette-Wagner, Bonny; Chasens, Eileen R; Sereika, Susan M; Burke, Lora E
Abstract: Study Objectives: The relationships between daytime sedentary behavior and that night's sleep and sleep and next day's sedentary behavior are unknown. The purpose of this analysis was to examine these potentially bidirectional associations. Methods: This study was a secondary analysis of baseline data from an ecological momentary assessment study to determine the triggers for dietary lapses during a weight loss intervention. Sedentary behavior, physical activity, and sleep were objectively measured using accelerometers. Linear mixed modeling was used to examine the bidirectional multivariate associations between activity and sleep characteristics for each outcome examined separately. The models included sex, age, body mass index (BMI), education, and day of the week (weekday vs. weekend). Results: Participants were predominantly white (81.5%) and female (88.9%) with a mean age of 51.2 ± 10.6 years. Longer previous night's total sleep time (TST) ( b = −0.320, standard error [SE] = 0.060; p < .001) and being a weekend ( b = −63.845, SE = 9.406; p < .001) were associated with less sedentary time the next day. More daytime sedentary time was associated with less wake after sleep onset ( b = −0.018, SE = 0.008; p = .016), fewer awakenings ( b = −0.010, SE = 0.004; p = .016), and less TST ( b = −0.060, SE = 0.028; p = .029) that night. Conclusions: The bidirectional relationships between sedentary time and sleep characteristics are complex and may vary depending on participant characteristics and duration of sedentary and sleep time. Interventions to decrease sedentary behavior may benefit by targeting sleep duration and weekday activity.